Jaringan dan komentar sebagai identifikasi potensi krisis pada video Youtube - Kurniawan, Bondan Kartiko; Sunarwinadi, Ilya Revianti; Berto, Agustinus Rusdianto (Jurnal Komunikasi Profesional, 2022)
Crisis can jeopardize the reputation and performance of the company. Crisis occurs when the results of the company’s operational activities do not meet the expectations of stakeholders. In a crisis, social media has a role both in disseminating information and as a means of expressing opinions and discussing. Video entitled RRI MENJADI MEDIA PROPAGANDA PKS DAN FPI? I Shelter CSW is a video on the YouTube social media platform that contains criticism of RRI performance which was uploaded on the Cokro TV channel on 19 May 2021. This video was motivated by the resignation of the President Director (Director) of Radio Republik Indonesia (RRI) in May 2021 after being requested by the Council Supervisors (Dewas) because they are considered to have committed a number of serious violations by not controlling the reporting of RRI. Even though the President Director has resigned, the fatal error is still a public discussion. Reports also appear on online sites and social media. This research was conducted using the method of social network analysis (SNA) to analyze the structure of networks, groups, and actors. This study succeeded in finding the network structure in the video comments column, which commented on the neutrality of RRI. Most of the comments made by the actors gave a negative assessment of RRI with the words RRI and Kadrun dominating the comments.